Quantitative Evaluation of Cytochrome P450 3A4 Inhibition and Hepatotoxicity in HepaRG 3-D Spheroids. (September 2018) - Shin, Dae-Seop; Seo, Hyewon; Yang, Jung Yoon; Joo, Jeongmin; Im, So Hee; Kim, Seong Soon; Kim, Sang Kyum; Bae, Myung Ae
Predicting drug–drug interactions (DDIs) is an important step during drug development to avoid unexpected side effects. Cytochrome P450 (CYP) 3A4 is the most abundant human hepatic phase I enzyme, which metabolizes >50% of therapeutic drugs. Therefore, it is essential to test the potential of a drug candidate to induce CYP3A4 expression or inhibit its activity. Recently, 3-dimensional (3-D) mammalian cell culture models have been adopted in drug discovery research to assess toxicity, DDIs, and pharmacokinetics. In this study, we applied a human 3-D spheroid culture protocol using HepaRG cells combined with liquid chromatography-tandem mass spectrometry (LC-MS/MS) to assess its ability to predict CYP3A4 inhibition. Levels of midazolam, a specific substrate of CYP3A4, were used to determine the long-term metabolic capacity of CYP3A4. Midazolam was decreased in the 3-D HepaRG culture system by ∼80% over 7 days, whereas its primary metabolite, 1-hydroxymidazolam, increased by ∼40%. Next, we assessed hepatotoxicity by determining the cytotoxicity of known hepatotoxicants in HepaRG spheroids, HepG2 cells, and primary human hepatocytes. Significant differences in cytotoxicity were detected in the system using 3-D HepaRG spheroids. These results suggest that 3-D HepaRG spheroids are a good model for prediction of CYP inhibition and hepatotoxicity in screening of early drug candidates.